Seasonal Hydration Status of Common Bryophyte Species in Azorean Native Vegetation - Márcia C. M. Coelho; Rosalina Gabriel; Claudine Ah-Peng (Plants, 2023)
Bryophytes play a crucial role in the ecosystem’s water compartment due to their unique ability to retain water. However, their role within temperate native ecosystems is mostly unknown. To address this knowledge gap, a study was conducted on Terceira Island (Azores), focusing on 14 bryophyte species found at different altitudes (40 m, 683 m, and 1012 m); five samples were collected monthly, per species and location, and their fresh, saturated, and dry weights were examined in the laboratory; four species were collected from more than one site. Generalized linear models (GLM) were used to assert the influence of climate factors (temperature, precipitation, and relative humidity) and environmental variables on two water indicators: field water content (FWC) and relative water content (RWC). None of the examined factors, per se, were able to explain all cases. Species appear to respond to climate according to a limiting factor effect: at lower elevations, precipitation was determinant, while at medium elevations, FWC was influenced by a combination of precipitation and relative humidity. At higher elevations, temperature was retained for seven of the nine studied species. The RWC values indicated that the 14 bryophyte species remained hydrated throughout the year but rarely reached their maximum water-holding capacity, even at the highest altitude. Understanding the mechanisms by which native bryophytes acquire, store, and release water is crucial for comprehending the resilience of native vegetation in the face of climate change. This knowledge can also enable the development of strategies to mitigate the effects of climate change and protect vital water resources.